MULTIKULTURALITAS DAN NARASI PRIMORDIAL DALAM POLITIK ELEKTORAL INDONESIA - Adrianus Aman; Pius Pandor (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2023)
The purpose of this article is to examine primordial issues in electoral political contestation in a plural Indonesian society. Electoral political contestation became a breeding ground for primordial issues. The majority wants to be led by a leader who is of the majority religion. Religious and tribal issues are used to win political contests. Indigenous and pagan narratives are echoed and lead to division. This aticle uses qualitative methodology with a leterer study approach referring to Emmauel Levinas' ethical theory of responsibility for analyzing data. The levinian ethic of responsibility expresses the idea of placing others as unique and different subjects altogether through their visible faces. The consequence is that the other must be respected and valued as subjects. At the same time the presence of others becomes the responsibility of